2019
DOI: 10.29303/jbt.v19i2.1390
|View full text |Cite
|
Sign up to set email alerts
|

Struktur Komunitas Karang Keras (Scleractinia) Di Zona Intertidal Pantai Mandalika Lombok Tengah

Abstract: Abstrak: Zona intertidal merupakan daerah pantai yang terletak antara pasang tertinggi dan surut terendah. Salah satu ekosistem yang terdapat di kawasan intertidal adalah ekosistem terumbu karang. Terumbu karang merupakan salah satu ekosistem laut yang menjadi sumber kehidupan bagi berbagai biota laut sehingga keberadaannya sangat penting, baik dari segi ekologis maupun ekonomis. Pantai Mandalika memiliki ekosistem terumbu karang dengan zona intertidal yang cukup luas. Pesatnya perkembangan wisata di Pantai Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
1
0
2
Order By: Relevance
“…In the coral reef ecosystem in P Gosong, Southwest Aceh, Family Faviidae has 3 genera with percentages between (Kongjandtre et al, 2012), and its presence has been reported in the southern Persian Gulf, the Gulf of Aden, Southeast Africa, and the Persian Gulf (Moradi et al, 2010). Reports related to its presence in Indonesian territory have been based on several research results by Nurhaliza et al (2019) in the intertidal zone of the Mandalika coast, Central Lombok, which has a percentage of up to 79%. Family Acroporidae, and Agariciidae are found with the same number of genera, namely 4 genera.…”
Section: Coral Conditionmentioning
confidence: 99%
“…In the coral reef ecosystem in P Gosong, Southwest Aceh, Family Faviidae has 3 genera with percentages between (Kongjandtre et al, 2012), and its presence has been reported in the southern Persian Gulf, the Gulf of Aden, Southeast Africa, and the Persian Gulf (Moradi et al, 2010). Reports related to its presence in Indonesian territory have been based on several research results by Nurhaliza et al (2019) in the intertidal zone of the Mandalika coast, Central Lombok, which has a percentage of up to 79%. Family Acroporidae, and Agariciidae are found with the same number of genera, namely 4 genera.…”
Section: Coral Conditionmentioning
confidence: 99%
“…Terumbu karang adalah salah satu ekosistem pesisir yang menjadi sumber kehidupan bagi berbagai macam biota laut sehingga keberadaannya sangat dibutuhkan, baik dari sudut pandang ekologi maupun ekonomi (Nurhaliza, Muhlis, Bachtiar, & Santoso, 2019). Perlindungan dan pengelolaan terumbu karang tidak hanya penting bagi habitat terumbu karang itu sendiri, tetapi juga bagi masyarakat lokal yang sangat bergantung padanya sebagai sumber daya alam.…”
Section: Pendahuluanunclassified
“…Restorasi karang masif masih belum dilakukan, meski karang masif merupakan komponen ekosistem terumbu yang penting. Karang masif sering ditemukan di zona intertidal dan perairan dangkal (Nurhaliza et al, 2019) dan memiliki strukturnya yang lebih kuat, tahan gelombang (Baldock et al, 2014) dan lebih tahan terhadap perubahan suhu (Loya, 2001).…”
Section: Pendahuluanunclassified